Sekularisme, Epistemologi Reformed, dan Liturgi: Menimbang Peran Liturgi dalam Konteks Masyarakat Sekuler - Jonathan, Samuel Vincenzo; Harsawibawa, Albertus (Societas Dei: Jurnal Agama dan Masyarakat, 2022)
Secularism is a condition of the times we live in today. It gives awareness to the global community that in reality there is only the immanentâ€”there is no God. So, theism is seen as just one of the many options available: atheism becomes even more attractive to embrace. Generally, a theist will respond by demonstrating the plausibility of theism through positive arguments for the existence of God. The author rejects this and offers an approach from Reformed epistemology, as a thesis on how one knows God, to the problem. Through Reformed epistemology, the author views secularism as what is understood as a cognitive environment. As a cognitive environment that prevents the â€œknowing subjectâ€ from knowing God, the authors point out that the appropriate response to secularism is to include the â€œknowing subjectâ€ into the liturgy. Thus, liturgy can also be understood as an act that has an epistemic dimension that enables a person to know God.